Economic adjustment within EMU: Ireland?s experience - MacCoille, Conall; McCoy, Daniel (Economic & Social Studies, 2002)
This paper examines the contribution of Balassa-Samuelson (B-S) type effects to inflationary pressures in Ireland. Irish productivity measures are exaggerated by foreign multinationals engaged in high value-added activities. These measures suggest that high productivity in the traded sectors explain most of the inflation differential. Using adjusted measures to account for the multinational effect, shorter-term demand side factors become more significant in explaining the inflation differential. Domestic fiscal and incomes policies are therefore an important source of adjustment for the Irish economy within a monetary union.
Keywords: European Monetary Union; Inflation; Quantitative methods; Ireland